Evaluation of a Prefabricated Fish Passage Design for Great Plains Fishes - Ryan M. Fitzpatrick; David W. Longrie; Ryan J. Friebertshauser; H. Paul Foutz (Fishes, 2023)
Connectivity is critical for stream fish persistence, and fish passage structures are a useful conservation tool to reconnect fragmented systems. The design of fish passage structures is a tradeoff between the area available for construction, slope, and costs associated with the structure. The Longrie–Fecteau fish passage structure was designed to be modular, adjustable to barrier-specific needs, and to have a low slope (2%) to pass small-bodied fishes. We evaluated fish passage through this structure in Fountain Creek, Colorado, USA, via a PIT tag mark–recapture study. We documented four native Great Plains fish species successfully ascending the passage structure, with most passage occurring at night. We estimated a 3% probability of a released fish entering the structure, then 89% and 99% passage to the midpoint and exit of the 123 m structure, respectively. Low entrance efficiency was due to low recapture probability of small-bodied study organisms in a relatively large system, and the low percentage of space of the entryway on this barrier (